A philosophical basis for hydrological uncertainty. Issue 9 (3rd July 2016) - Nearing, Grey S.; Tian, Yudong; Gupta, Hoshin V.; Clark, Martyn P.; Harrison, Kenneth W.; Weijs, Steven V.
ABSTRACT: Uncertainty is an epistemological concept in the sense that any meaningful understanding of uncertainty requires a theory of knowledge. Therefore, uncertainty resulting from scientific endeavors can only be properly understood in the context of a well-defined philosophy of science. Our main message here is that much of the discussion about uncertainty in hydrology has lacked grounding in these foundational concepts, and has resulted in a controversy that is largely the product of logical errors rather than true (axiomatic) disagreement. As an example, we explore the current debate about the appropriate role of probability theory for hydrological uncertainty quantification. Our main messages are: (1) apparent (and/or claimed) limitations of probability theory are not actually consequences of that theory, but rather of deeper underlying epistemological (and ontological) issues; (2) questions about the appropriateness of probability theory are only meaningful if posed as questions about our preferred philosophy of science; and (3) questions about uncertainty may often be better posed as questions about available information and information use efficiency. Our purpose here is to discuss how hydrologists might ask more meaningful questions about uncertainty.